Decolonial Perspectives from Latin America: Initial Core Concepts and Special Issue Announcement - Zambonini, Juan Pedro; Tosto, Virginia (Voices: A World Forum for Music Therapy, 2024)
This editorial discusses specific coordinates for thinking about decolonial perspectives from Latin America. It explores the notions of academic dependence, epistemic colonialism and situated thought as axes within the decolonial perspective. It also extends an invitation to Latin American music therapists to participate in a special edition to be published in 2025. Lastly, a brief description of the articles included in this journal edition is provided. Resumen Este editorial contempla certas coordenadas para pensar sobre as perspectivas decoloniais da América Latina. Ele explora as noções de dependência acadêmica, colonialismo epistêmico e pensamento situado como eixos dentro da perspectiva decolonial. Também faz um convite aos musicoterapeutas latino-americanos para participarem de uma edição especial a ser publicada em 2025. Por fim, é apresentada uma breve descrição dos artigos incluídos nesta edição da revista. Resumen Esta editorial contempla ciertas coordenadas para pensar las perspectivas decoloniales desde Latino America. Explora las nociones de dependencia academica, colonialismo epistemico y pensamiento situado como ejes dentro de la perspectiva decolonial. Asimismo, se extiende una invitacion a musicoterapeutas latinoamericanos para ser parte de una edición especial que será publicada en 2025. Por ultimo, se brinda una breve descripción de los artículos incluidos en esta edición de la revista.